Fiscal multipliers in the Eurozone: an SVAR analysis - Afonso, António (2022)
We compute the value of fiscal multipliers (for government primary expenditure, Income and wealth taxes and for Production and import taxes) in the Eurozone countries since the creation of the currency union (2000Q1-2016Q4), in order to understand how the values can vary according to the public debt level, the pace of economic growth, and the output gap. Imposing quarterly fiscal shocks, the results showed that government expenditure had a positive effect on output, with an annual accumulated multiplier of 0.44, whereas tax multipliers presented negative signs: the Income and wealth and the Production and import taxes stood at −0.11 and −0.55, respectively. Furthermore, the spending multiplier showed a higher value for countries with lower levels of public debt, during recessions, and in countries with negative output gaps. On the other hand, tax shocks seemed to be recessive in highly indebted countries and those facing positive output gaps.